Design and Operational Test of Large-sized HTS Magnets with Conduction Cooling System for a 300 kW-class Superconducting Induction Heater. (4th June 2018) - Choi, Jongho; Kim, S. K.; Cho, Sangho; Park, Minwon; Yu, In-Keun
Abstract: In this paper, we presented design specifications and operational test results of large-sized high temperature superconducting (HTS) magnets for Superconducting Induction Heater (SIH). HTS magnets were designed and fabricated with the metal insulation method. Critical currents of the HTS magnets were estimated by considering the angular dependency on the magnetic flux density of HTS tape. The characteristic resistance, the charging and discharging time were calculated and measured in the liquid nitrogen and the conduction cooling condition achieved with the 2nd stage GM cryo-cooler. The saturated temperature of the HTS magnet reached at 5.6 K. The performances of the large-sized HTS magnet including cooling and magnetic field characteristics were tested under the conduction cooling. These results were evaluated with those of finite element method analysis results. The characteristic analysis results of the large-sized HTS magnets will be applied for development of the commercial 300 kW SIH.